1995
DOI: 10.1016/0005-2736(95)00076-f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-chain alcohols on the phase behavior and interdigitation of phosphatidylcholine bilayer membranes

Abstract: Solute effects on the polymorphism and phase transitions in the suspensions of dipalmitoylphosphatidylcholine (DPPC) were studied by means of carboxyfluorescein (CF) and phosphatidylethanolamine rhodamine (PERho) fluorescence, differential scanning calorimetry, and X-ray diffraction. Specifically, the shifts of the lipid chain-melting phase transition, pretransition and subtransition temperature as a function of the bulk alcohol concentration were determined calorimetrically. The chain-melting phase transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
0
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 30 publications
11
106
0
6
Order By: Relevance
“…GIXD experiments have shown that the effective area per head group decreases with an increase in ethanol concentration leading to a reduction of the chain tilt angle. The influence of ethanol on self-assembled aggregates of phospholipid molecules has been reported in [33][34][35][36][37][38][39]. In these investigations, lipid bilayers dispersed as unilamellar or multilamellar vesicles in an aqueous solution have been used.…”
Section: Influence Of the Head Groupmentioning
confidence: 99%
“…GIXD experiments have shown that the effective area per head group decreases with an increase in ethanol concentration leading to a reduction of the chain tilt angle. The influence of ethanol on self-assembled aggregates of phospholipid molecules has been reported in [33][34][35][36][37][38][39]. In these investigations, lipid bilayers dispersed as unilamellar or multilamellar vesicles in an aqueous solution have been used.…”
Section: Influence Of the Head Groupmentioning
confidence: 99%
“…In particular, the carbonyl groups of the glycerol backbone of phospholipids are thought to be the favored hydrogen bonding sites for ethanol [40]. Ethanol displaces water when it adsorbs to the head group, which increases the head group volume and decreases the order of the hydrocarbon chains [13,41,42]. The increase in head group volume leads to increased chain tilting and creates energetically unfavorable voids in the hydrocarbon region of non-interdigitated membranes, encouraging the creation of the L I phase at high concentrations [13,39,[42][43][44].…”
Section: Chemically-induced Interdigitation Of Phosphatidylcholinesmentioning
confidence: 99%
“…Ethanol displaces water when it adsorbs to the head group, which increases the head group volume and decreases the order of the hydrocarbon chains [13,41,42]. The increase in head group volume leads to increased chain tilting and creates energetically unfavorable voids in the hydrocarbon region of non-interdigitated membranes, encouraging the creation of the L I phase at high concentrations [13,39,[42][43][44]. Once the L I phase is formed, ethanol can bind to the exposed hydrocarbon chains, replacing the unfavorable interaction of the acyl chains with water [45].…”
Section: Chemically-induced Interdigitation Of Phosphatidylcholinesmentioning
confidence: 99%
“…To study the effect of these molecules on the properties studies on various model membranes have been carried out by various groups [66,[71][72][73][74][75][76]. These studies show that at low temperatures adding alcohol leads the formation of an interdigitated or L βI phase in stead of the commonly formed L c or L β (gel phases).…”
Section: Effect Of Alcoholmentioning
confidence: 99%
“…The critical bulk concentration at which interdigitation is complete decreases with increasing length of the alcohol [71,75,77]. Various theories have been used to relate the bulk concentration of alcohol to the concentration in the lipid.…”
Section: Effect Of Alcoholmentioning
confidence: 99%